Microbial detoxification of lignocellulosic biomass hydrolysates: Biochemical and molecular aspects, challenges, exploits and future perspectives - Ujor, Victor C.; Okonkwo, Christopher C. (Frontiers in Bioengineering and Biotechnology, 2022)
Valorization of lignocellulosic biomass (LB) has the potential to secure sustainable energy production without impacting food insecurity, whist relieving over reliance on finite fossil fuels. Agro-derived lignocellulosic residues such as wheat straw, switchgrass, rice bran, and miscanthus have gained relevance as feedstocks for the production of biofuels and chemicals. However, the microorganisms employed in fermentative conversion of carbohydrates to fuels and chemicals are unable to efficiently utilize the sugars derived from LB due to co-production of lignocellulose-derived microbial inhibitory compounds (LDMICs) during LB pretreatment. LDMICs impact microbial growth by inhibition of specific enzymes, cause DNA and cell membrane damage, and elicit cellular redox imbalance. Over the past decade, success has been achieved with the removal of LDMICs prior to fermentation. However, LDMICs removal by chemical processes is often accompanied by sugar losses, which negatively impacts the overall production cost. Hence, in situ removal of LDMICs by fermentative organisms during the fermentation process has garnered considerable attention as the ‘go-to’ approach for economical LDMICs detoxification and bio-chemicals production. In situ removal of LDMICs has been pursued by either engineering more robust biocatalysts or isolating novel microbial strains with the inherent capacity to mineralize or detoxify LDMICs to less toxic compounds. While some success has been made along this line, efficient detoxification and robust production of target bio-chemicals in lignocellulosic hydrolysates (LHs) under largely anaerobic fermentative conditions remains a lingering challenge. Consequently, LB remains an underutilized substrate for bio-chemicals production. In this review, the impact of microbial LH detoxification on overall target molecule production is discussed. Further, the biochemical pathways and mechanisms employed for in situ microbial detoxification of furanic LDMICs [e.g., furfural and 5-hydroxymethylfurfural (HMF)] and phenolic LDMICs (e.g., syringaldehyde, p-coumaric acid, 4-hydroxybenzaldehyde, vanillin, and ferulic acid) are discussed. More importantly, metabolic engineering strategies for the development of LDMIC-tolerant and bio-chemicals overproducing strains and processes are highlighted.